Emigration and Its Economic Impact on Eastern Europe - Atoyan, Ruben (Staff Discussion Notes; Staff Discussion Notes ;, 2016)
This paper analyses the impact of large and persistent emigration from Eastern European countries over the past 25 years on these countries' growth and income convergence to advanced Europe. While emigration has likely benefited migrants themselves, the receiving countries and the EU as a whole, its impact on sending countries' economies has been largely negative. The analysis suggests that labor outflows, particularly of skilled workers, lowered productivity growth, pushed up wages, and slowed growth and income convergence. At the same time, while remittance inflows supported financial deepening, consumption and investment in some countries, they also reduced incentives to work and led to exchange rate appreciations, eroding competiveness. The departure of the young also added to the fiscal pressures of already aging populations in Eastern Europe. The paper concludes with policy recommendations for sending countries to mitigate the negative impact of emigration on their economies, and the EU-wide initiatives that could support these efforts.